Art and Wound Healing: van Gogh Cypresses-like Lipodermatosclerosis. (December 2016) - Papi, Massimo
Lipodermatosclerosis may develop clinical aspects that have striking analogies with Van Gogh's style of painting cypresses. They may reveal specific physiopathological disorders and identify a homogeneous group of patients with chronic venous insufficiency.